Concentration measurements and isotopic composition of airborne molybdenum collected in an urban environment - Lane, S.; Proemse, Bernadette; Tennant, A.; Wieser, M. (Springer, 2013)
Here, we report the first measurements of the molybdenum (Mo) isotopic composition of aerosols collected on Teflon air filters. Mo concentrations and isotopic compositions were measured at selected locations in the city of Calgary, Canada, including a residence, theisotope laboratory at the University of Calgary, the University of Calgary weather station, and the City of Calgary Transit bus garage. Concentrations ranged from 0.07 ng/m3 in the laboratory to 19.0 ng/m3 in the bus garage. The concentrations of Mo in the air samplescollected in the bus garage were the highest measured in this study. To date, there are no reported data for the Mo isotopic composition of airborne Mo. In this study, the d98/95Mo values measured for the different urban sampling sites and reported relative to SRM 3134, ranged from -0.18 to +0.94 ‰. The results of this investigation suggest that measurements of Mo concentrations and isotopic compositions have the potential to trace anthropogenic emissions in an urban environment.